1995
DOI: 10.1002/macp.1995.021960909
|View full text |Cite
|
Sign up to set email alerts
|

Conformational properties of the amphipathic lytic polypeptide bombolitin II. A circular dichroism, NMR and computer simulation study

Abstract: Bombolitin I1 is a member of a family of five structurally related heptadecapeptides, originally isolated from the venom of a bumblebee, acting at the membrane level and able to increase the activity of phospholipase A,. The biological activity of bombolitins seems to be related to their ability to form amphipathic helical structures. To complete our systematic studies on this class of peptides, in the present work we synthesized bombolitin I1 by solid phase methodology. The secondary structure of this peptide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 29 publications
0
15
0
Order By: Relevance
“…The behaviors of these small membrane peptides are interesting with the comparison of the behavior of the large transmembrane peptides. Among them, Bombolitin II (BLT2), one of the Bombolitins family, has a small size with only 17 amino-acid residues (13)(14)(15)(16)(17)(18)(19)(20)(21). This peptide is hemolytic heptadecapeptides originally isolated from bumblebee venom.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The behaviors of these small membrane peptides are interesting with the comparison of the behavior of the large transmembrane peptides. Among them, Bombolitin II (BLT2), one of the Bombolitins family, has a small size with only 17 amino-acid residues (13)(14)(15)(16)(17)(18)(19)(20)(21). This peptide is hemolytic heptadecapeptides originally isolated from bumblebee venom.…”
Section: Introductionmentioning
confidence: 99%
“…To understand the hemolytic activity of the peptide, elucidation of structure and orientation of BLT2 molecules bound to membranes is certainly important. Battistutta et al (16) performed a computer simulation study of BLT2 that adopts an amphipathic helical structure in a dilute aqueous solution of sodium dodecyl sulfate. The MD simulation of BLT2 was performed by Monticelli et al (20) in a membrane mimetic environment.…”
Section: Introductionmentioning
confidence: 99%
“…The bombolitins are similar in terms of function and primary structure, especially bombolitins I-III (BLT1-BLT3). It was reported that they assume different secondary structures dependent upon solution conditions such as pH, ionic strength, and peptide concentration [130][131][132], and they adopt predominantly α-helical structure in solutions containing SDS micelles [130,131]. The α-helix in the N-terminal region of BLT3 is stabilized by a salt bridge between Lys2 and Asp5 (residues identical in the sequence of BLT2) at neutral pH [133].…”
Section: Bombolitin IImentioning
confidence: 98%
“…The bombolitin family of oligopeptides contains five species with 17-residue sequences derived from bumblebee venom. Their conformations are helical but largely disordered in aqueous solution; in the presence of bilipid membranes, they take on a more ordered, alpha helical structure according to CD studies (19,20). At high concentrations, above 2.5 mM, and in the presence of SDS, the peptides form aggregates (21).…”
Section: Ev)mentioning
confidence: 99%